The concept of ritual in Confucian thought and its implications for social order - Xinying Wu; Ying Zhao (Trans/Form/Ação)
“Ritual” is one of the core concepts in Confucian culture. Duke Zhou developed the notion of “ritual” as a set of behavioral norms to maintain the hierarchical system of the ancestral lineage and as regulations for state governance and ceremonial practices. Pre-Qin Confucianism inherited and innovated the Zhou rituals, forming the influential Confucian ritual system deeply embedded in traditional Chinese society. The ritual system embodies elements of absolute monarchy, ancestral reverence and filial piety, reflecting China’s traditional cultural factors. It holds significant social functions, serving as a powerful tool for maintaining social order, promoting stability and ensuring the well-being of future generations. This article starts with the three main aspects of the relationship between benevolence and ritual, governance through virtue, and ritual and law. It explains the spirit of benevolence, people-friendly political ethics and the inherent morality of the law contained in Confucian etiquette ethics, and further analyzes the modern value of Confucian etiquette culture and spirit to the contemporary Chinese society’s moral construction and legal one.